2011
DOI: 10.1007/s10763-010-9231-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Turkish High School Chemistry Textbooks and Teacher-Generated Questions About Gas Laws

Abstract: This study presents the results of an analysis of high school chemistry textbooks and teacher-generated questions about gas laws. The materials that were analyzed consisted of 456 questions about gas laws found in seven grade 10 chemistry textbooks and 264 teacher-generated examination questions prepared by seven chemistry teachers from three schools. These questions were classified into three categories (recall, algorithmic, and conceptual); the conceptual questions (ConQ) were further classified into six sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
0
13
0
3
Order By: Relevance
“…Hence, these skills include problem solving, 5,7 decision making, 3,5,7 critical thinking, 5,7 the ability to ask complex questions, 1,3,7 generating argumentation 1,3 and systems thinking. 3,7 In our opinion, a very detailed definition of systems thinking is that proposed by Salisbury. 8 This author defined systems thinking as the ability to think about all the concepts and relations that exist within a system, in order to effectively structure these relations.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these skills include problem solving, 5,7 decision making, 3,5,7 critical thinking, 5,7 the ability to ask complex questions, 1,3,7 generating argumentation 1,3 and systems thinking. 3,7 In our opinion, a very detailed definition of systems thinking is that proposed by Salisbury. 8 This author defined systems thinking as the ability to think about all the concepts and relations that exist within a system, in order to effectively structure these relations.…”
Section: Introductionmentioning
confidence: 99%
“…Bu sonuç katılımcıların ilgili kavramın ne olduğundan ziyade deniz seviyesi ve 0 0 C deki değerinin ne olduğuna odaklandıklarını göstermektedir. Bu sonucun ortaya çıkması; kitaplarda açık hava basıncının detaylı tanımına çok az yer verilmesine karşın deniz seviyesi ve 0 0 C de açık hava basıncı ile ilgili benzer tarzdaki sayısal işlem gerektiren problemlere çok sıklıkla yer verilmesi ile açıklanabilir (de Berg, 1989;Wiebe, ve Stinner, 2010;Nakiboğlu ve Yıldırır, 2011;Gillette ve Sanger, 2014;Gegios, Salta ve Koinis, 2017). Nitekim katılımcıların açıklamalarından alınan "KÖ19: açık hava basıncı 76cmHg'dir, L18: açık hava basıncı 0 0 C de, deniz seviyesinde yapılan basınca denir" şeklindeki ifadeler bunu desteklemektedir.…”
Section: Sonuç Tartişma Ve öNeri̇lerunclassified
“…Lise ve üniversite seviyesinde atmosfer basıncından daha çok kapalı kaplardaki gaz basıncı konusuna ve kinetik teoriye yer veriliyor olması ve ayrımın yeterince yapılmaması öğrencilerin atmosfer basıncı ve onunla ilgili faktörleri açıklarken kapalı kaplardaki gaz basıncı ile karıştırmalarına neden olmaktadır (Hacioglu, Durukan ve Cigdem, 2016). Ayrıca ders kitaplarında basınç konusu ile ilgili yetersiz ve hataya sevk edecek açıklamaların yurt içinde ve yurt dşında birçok araştırmada ortaya konulduğu görülmektedir (Şahin, 2001;Aksoy, 2003;Ayas, Karataş ve Çoştu 2003;Nakiboğlu ve Yıldırır, 2011;Gillette ve Sanger, 2014). Bunun yanı sıra ders kitaplarındaki açık hava basıncı ile ilgili sorular incelendiğinde diğer konulara benzer şekilde bu konu ile ilgili kavramlar arası ilişkileri açıklamayı içeren sorular yerine matematiksel işlem içerikli soruların bulunduğu görülmektedir (Nakiboğlu ve Poyraz, 2004;Nakiboğlu ve Yıldırır, 2011).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Nakiboglu et al, analyzed grade-10 school chemistry textbooks' questions in Turkey [9]. They found that most of the questions did not enable students to develop conceptual understanding and gain higher-order cognitive skills.…”
Section: Introductionmentioning
confidence: 99%